Lydia Chukovskaya’s Sofia Petrovna Is Going Under and Abroad - Klots, Yasha (Wiener Slawistischer Almanach, 2021)
The essay treats Lydia Chukovskaya’s novella Spusk pod vodu (Going Under) as an amplification of the historical context, subject matter, and setting of Sofia Petrovna, Chukovskaya’s earlier and more acclaimed work of fiction. Reconstructing the history of the first publication and reception of Going Under abroad in 1972, the essay argues that the two works, set and written ten years apart, form a cycle: they are “indexical” to each other, and irreducible to the respective historical contexts that inform their subject matter. Through a close examination of Going Under vis-a-vis Sofia Petrovna, the essay dwells, in particular, on literary paradigms on both sides of the Soviet borders, situating gosizdat and tamizdat in a relationship of mutual complementarity, rather than binary opposition.